Technologies integration for distributed manufacturing scheduling in a virtual enterprise - Vieira, Gaspar (2012)
Distributed scheduling problems are challenging tasks to researchers and practitioners that have been gaining increasing popularity over the years. This is partly attributed to the fact that multi-site production and networked manufacturing environments are increasing as a consequence of globalisation. In this paper a system for technologies integration for supporting distributed scheduling in a Virtual Enterprise, by combining a simulation-based approach, with the Hungarian algorithm, for solving job-shop scheduling problems is presented, in order to show how we can benefit from this combination of procedures for distributed manufacturing scheduling.